PENGUATAN KAPASITAS MANAJEMEN KELOMPOK USAHA ARIKA AMA ORY MELALUI PELATIHAN PARTISIPATIF DI DESA PASSO, KOTA AMBON - Damanik, Inta P. N.; Tahitu, Meilvis E. (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Universitas Pattimura, 2025)
The purpose of this community service activity is to help the Arika Ama Ory group improve their group management capacity includes planning, organizing, implementing, and monitoring and evaluating group activities with method of the activity consists of identifying problems, socialization, and training. The participants of the activity were all members of the Arika Ama Ory group, totaling 12 housewives. The increase in group management capacity was analyzed based on the results of the pretest and posttest. The results of the pretest and posttest showed that knowledge, attitudes, and skills in managing groups increased, which was manifested through the group's success in preparing group plans including plans for organizing activities, implementing activities, and monitoring/evaluating activities. It can be concluded that participatory socialization and training methods can significantly increase the management capacity of the Arika Ama Ory group. Furthermore, mentoring is needed so that the behavioural changes that have occurred can be internalized in the members of the Arika Ama Ory group. Mentoring can be carried out by the Passo Village Government, universities through various field activities of lecturers and students, and other parties involved in the development of rural human resources.